Performance assessment of irregular RC buildings with shear walls after Earthquake - Kocak, Ali; Zengin, Basak; Kadioglu, Fethi (PERGAMON-ELSEVIER SCIENCE LTD, 2015)
This paper discusses the behavior of frame-wall irregularity on established existing reinforced concrete (RC) structures that were subjected to the 1999 Kocaeli Earthquake in Turkey. In particular, reference is made to the nonlinear static analysis and nonlinear dynamic analysis of reinforced concrete (RC) structures containing shear walls. The layered shell model has been chosen due to its advantages. The damage observed after reconnaissance studies has been captured using the 3D model. The imperfections that the irregularity effects caused are discussed throughout the paper. (C) 2015 Elsevier Ltd. All rights reserved.
Keywords: Nonlinear static procedures; Pushover; Time history; Shear wall; Irregular RC building; MODAL PUSHOVER ANALYSIS; SEISMIC DEMANDS; Engineering; Materials Science